Effectiveness of Designing an Electronic Course for the Subject of General Physics According to the Brain-based Learning Theory on the Achievement of Basic Education Colleges Students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aim of the Study: Effectiveness of Designing an Electronic Course for the Subject of General Physics According to the Brain-based Learning Theory on the Achievement of Basic Education Colleges Students.The researcher used the experimental method to examine its effectiveness after the end of the experiment on increasing students’ achievement in general physics. The researcher adopted an experimental design of partial control with two equal groups: experimental and control. According to this design, a random research sample was selected from the research population representing students of the Faculties of Basic Education in Iraq - College of Basic Education, University of Babylon, Department of General Sciences- the first grade. The two group were equal in terms of the following variables: age (calculated in months), intelligence, and parents’ achievement. The study subject included all the items of the general physics. The behavioral objectives of this course were drafted; they were as (110) objectives in number. To make a research tool, the researcher conducted an achievement test in general physics consisting of (50) objective multiple choice items of 4 alternatives. After applying the search tool and analyzing the results obtained statistically by the researcher using Microsoft Excel and SPSS software, the results showed that the students of the experimental group outperformed the students of the control group in the physical knowledge test.